Un modelo democrático de justicia constitucional local - Enríquez Soto, Pedro Antonio (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
The contemporary constitutional state in the world has placed constitutions at the highest rung of the normative universe of each state; Kelsen placed the Constitution at the apex of the legal pyramid. Thus, the Constitution constitutes the formal and material normative document that each material in the exercise of sovereignty is given for itself, in order to organize and fulfill the purposes for which it was created. With the Constitution begins the "must be" of a state, is the first rule and therefore, is not preceded by another. In this attribute lies its constituent quality because once established the normative order is initiated and developed, it creates the normative production organs and delimits its competences. This constitutive characteristic of the Constitution gives it the character of supreme, because from it emanates the entire secondary legal system that will give existence and validity to the general precepts enshrined in the founding norm. The constitutional supremacy, comes from that character constituent of the fundamental charter, when giving origin to the generation or the national legal system. However, the supremode nature of the Constitution, by itself does not guarantee the validity and respect of its text; The public power in the exercise of its powers may violate or disrupt constitutional principles, executing acts or omissions contrary to it. The present study is intended to study the system of local constitutional justice in Mexico, which arises from the promulgation of the Constitution of Veracruz in 2000, expanding to several federal federal entities, as if it were a constitutional fashion Or imitation of the modern, without the reflection, analysis and weights necessary to achieve its social social effectiveness and relevance in a democratic state.

El estado constitucional contemporáneo en el mundo ha ubicado a las constituciones en el más alto peldaño del universo normativo de cada estado; Kelsen situó a la Constitución en el vértice de la pirámide jurídica. Así, la Constitución, constituye el documento normativo formal y material que cada material estado en ejercicio de la soberanía se da para sí, con el objeto de organizarse y cumplir con los fines para los cuales se creó. Con la Constitución se inicia el “deber ser” de un estado, es la primera norma y por lo mismo, no es precedida por otra. En este atributo reside su cualidad constituyente porque una vez establecida se inicia y se desarrolla el orden normativo, crea los órganos de producción normativa y delimita sus competencias. Esta característica constituyente t de la Constitución, le da el carácter de suprema, porque de ella emana todo el sistema jurídico secundario que dará existencia y validez a los preceptos generales consagrados en la norma fundante. La supremacía constitucional, deviene de ese carácter constituyente de la carta fundamental, al dar origen a la o generación del sistema jurídico nacional. Sin embargo, el carácter supremo de la Constitución, por sí solo no garantiza la vigencia y respeto de su texto; el poder público en el ejercicio de sus atribuciones puede violentar o trastocar los principios constitucionales, ejecutando actos u omisiones contrarios a ella. La presente investigación tiene por objeto de estudio el sistema de i justicia constitucional local en México, que surge a raíz de la promulgación de la Constitución de Veracruz en el año 2000, expandiéndose a varias entidades federal federativas, como si se tratara de una c moda constitucional o imitación de lo moderno, sin la reflexión, análisis y ponderaciones necesarias para lograr su social efectividad social y pertinencia en un estado democrático.
Facultad de Derecho y Ciencias Sociales. Doctorado interinstitucional en Derecho
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/881; info:eu-repo/classification/cti/5; FDCS-D-2008-0653; Constitución; Justicia; Régimen; Local